Pain is a major component of quality of life in patients with ankylosing spondylitis and the possibilities of its relief - Oksana Anatolyevna Pirogova; Т А Raskina; М V Letaeva (Современная ревматология, 2013)
The paper gives the results of an investigation of quality of life (QL) in patients with ankylosing spondylitis. It shows the implication of chronic pain syndrome in lowering QL and considers the issues of combination therapy with nimesulide (nise) and tizanidine (sirdalud) for pain syndrome.